Targeting the circBMPR2/miR-553/USP4 Axis as a Potent Therapeutic Approach for Breast Cancer - Yiran Liang; Xiaojin Song; Yaming Li; Tingting Ma; Peng Su; Renbo Guo; Bing Chen; Hanwen Zhang; Yuting Sang; Ying Liu; Yi Duan; Ning Zhang; et al. (Elsevier, 2019)
Emerging evidence suggests that circular RNAs (circRNAs) have crucial roles in various processes, including cancer development and progression. However, the functional roles of circRNAs in breast cancer remain to be elucidated. In this study, we identified a novel circRNA (named circBMPR2) whose expression was lower in breast cancer tissues with metastasis. Moreover, circBMPR2 expression was negatively associated with the motility of breast cancer cells and significantly downregulated in human breast cancer tissues. Functionally, we found that circBMPR2 knockdown effectively enhanced cell proliferation, migration, and invasion. Moreover, circBMPR2 knockdown promoted tamoxifen resistance of breast cancer cells through inhibiting tamoxifen-induced apoptosis, whereas circBMPR2 overexpression led to decreased tamoxifen resistance. Mechanistically, we demonstrated that circBMPR2 could abundantly sponge miR-553 and that miR-553 overexpression could attenuate the inhibitory effects caused by circBMPR2 overexpression. We also found that ubiquitin-specific protease 4 (USP4) was a direct target of miR-553, which functions as a tumor suppressor in breast cancer. Our findings demonstrated that circBMPR2 might function as a miR-553 sponge and then relieve the suppression of USP4 to inhibit the progression and tamoxifen resistance of breast cancer. Targeting this newly identified circRNA may help us to develop potential novel therapies for breast cancer patients. Keywords: breast cancer, circBMPR2, tumor suppressor, tamoxifen resistance, miR-553, USP4